“Diseño de procesos para la elaboración de caramelos duros en la empresa alimentos DUCROMZ”. - Cuyo Semblantes, David Wilfrido (2021)
The research work was carried out at Alimentos Ducromz Cia. Ltda., with the purpose of solving the lack of protocols in production. In the initial diagnosis, surveys and cause-effect diagrams were used, verifying the inadequacies in the production process, lack of procedures and control parameters. It was considered for the research problem the lack of a design of production processes for the production of hard candies that limits business productivity. The types of research used for the development of the research project are: bibliographic, field and descriptive. The scientific research methods used are synthetic analytical and deductive inductive. The methodology used for the development of the research project is: The study of the characteristics of the company and the diagnosis of the entire production process, then the proposal of all processes was made taking into account the INEN 2217 standard for confectionery products, the technical staff and operators were trained on the procedures to be taken into account at each stage of the production processes. The main results obtained are: elaboration of the process design for hard candy, description of the activities and determination of control parameters. As a fundamental conclusion, it has been considered that it is of vital importance to have a process design for the production of hard candies, which would be a great contribution to the production process of Alimentos Ducromz.